Impact of pulsed electric field (PEF) pretreatment on process performance of industrial French fries production. (October 2018) - Fauster, T.; Schlossnikl, D.; Rath, F.; Ostermeier, R.; Teufel, F.; Toepfl, S.; Jaeger, H.
Abstract: The application of pulsed electric fields in industrial scale potato processing was investigated regarding its impact on process performance and product quality. The PEF induced cell disintegration was measured by impedance analysis and texture softening was analyzed by cutting force measurements. Softening of the tissue was found to improve the cutting behavior leading to a smoother cutting surface and up to 80% less feathering. Thereby, starch loss was reduced and a significant reduction of fat uptake from 7.5 to 6.8% was found. The breaking loss decreased significantly from 11.0 to 6.0% regardless of the applied energy input (0.2–1.0 kJ/kg), due to improved elastic properties of the potato sticks. No effect was detectable on the peeling behavior of potato and on rheological characteristics of processing by-products such as puree, although the lump formation in puree produced from PEF pretreated potato increased. Overall, PEF was shown to deliver similar and higher quality improvements conventionally achieved by applying thermal preheating at much lower energy consumption. Highlights: Impact of PEF on relevant quality parameters for French fries validated in industrial scale. Beneficial effects already at low treatment intensities (E = 1.0 kV/cm, W = 0.2 kJ/kg). Improved cutting surface properties. Reduction of starch loss during cutting after PEF pre-treatment. Decrease of fat content for PEF treated pre-fried fries in comparison to untreated samples.